Finite element simulation and process optimization of microstructure evolution in the formation of Inconel 718 alloy bolts. (30th November 2018) - Li, Changmin; Tan, Yuanbiao; Zhao, Fei
Abstract: To optimize the production process of Inconel 718 superalloy bolts, the uniformity of the microstructure and the mechanical properties are improved. In this paper, the finite element model is first established by a Gleeble thermal compression experiment, and the reliability of the model is verified by DEFORM-3D software. The microstructure evolution of the bolt-forming process is simulated and verified by a trial production. The simulation results show that with increasing deformation temperature, the dynamic recrystallization fraction increases, and the head microstructure becomes more uniform in the region with large strain. Deformation at 1150 °C is more conducive for obtaining a uniform microstructure. A good fit can be found by comparing the trial production results with the simulation results using the optimized process parameters. The finite element model can provide guidance for the process optimization and prediction of the microstructure and properties of alloy bolts.